2019
DOI: 10.1038/s41598-019-53628-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of food on the pharmacokinetics and therapeutic efficacy of 4-phenylbutyrate in progressive familial intrahepatic cholestasis

Abstract: Progressive familial intrahepatic cholestasis (PFIC), a rare inherited disorder, progresses to liver failure in childhood. We have shown that sodium 4-phenylbutyrate (NaPB), a drug approved for urea cycle disorders (UCDs), has beneficial effects in PFIC. However, there is little evidence to determine an optimal regimen for NaPB therapy. Herein, a multicenter, open-label, single-dose study was performed to investigate the influence of meal timing on the pharmacokinetics of NaPB. NaPB (150 mg/kg) was administere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 32 publications
(43 reference statements)
1
13
0
Order By: Relevance
“…However, in a small study in 7 patients with PFIC-1 and -2 treated with 4-PBA no adverse events were reported even after dose escalation. 95 Correction and restoration of the activity of ABCB4 variants, although in vitro, provide interesting leads in the context of personalised medicine. Recently, ivacaftora cystic fibrosis transmembrane conductance regulator (CFTR) potentiatorwas shown to rescue defective phosphatidylcholine secretion activity.…”
Section: Key Pointmentioning
confidence: 99%
“…However, in a small study in 7 patients with PFIC-1 and -2 treated with 4-PBA no adverse events were reported even after dose escalation. 95 Correction and restoration of the activity of ABCB4 variants, although in vitro, provide interesting leads in the context of personalised medicine. Recently, ivacaftora cystic fibrosis transmembrane conductance regulator (CFTR) potentiatorwas shown to rescue defective phosphatidylcholine secretion activity.…”
Section: Key Pointmentioning
confidence: 99%
“…The last patient showed no clear response to NaPB therapy in the first 12 months. Therefore, the regimen was switched to preprandial oral administration, and the beneficial effects of NaPB therapy were observed . The change in the liver histology of this patient in the first 12 months after the beginning of NaPB therapy was determined as “deteriorated” by all pathologists, but in the next 12 months it was evaluated as “unchanged” by two pathologists and “improved” by the other (Table S4; see Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The period between each biopsy was 12 months. Their detailed clinical courses have been published elsewhere . One patient showed a good clinical response to NaPB with improved serological findings, including bilirubin, while the other showed no obvious improvement in 12 months after starting postprandial oral administration of NaPB.…”
Section: Methodsmentioning
confidence: 99%
“…Pre-breakfast, rather than post-breakfast, oral administration markedly increased systemic exposure of PB and decreased plasma glutamine availability after breakfast in the healthy adults [6] . In the pediatric patients with PFIC, we found that food intake before oral administration of NaPB reduced plasma PB levels and diminished its therapeutic efficacy through a choleretic effect [7] , another pharmacological action of NaPB [10] , [11] , [12] . Importantly, there were no severe adverse events attributable to preprandial oral administration of NaPB.…”
Section: Introductionmentioning
confidence: 84%
“…We have identified an interaction between NaPB and food in healthy adults [6] and in pediatric patients with progressive familial intrahepatic cholestasis (PFIC) [7] , a rare inherited autosomal recessive liver disease [8] , [9] . Pre-breakfast, rather than post-breakfast, oral administration markedly increased systemic exposure of PB and decreased plasma glutamine availability after breakfast in the healthy adults [6] .…”
Section: Introductionmentioning
confidence: 99%